PENGARUH SPIP DAN EFEKTIVITAS INTERNAL AUDIT TERHADAP PENCEGAHAN KORUPSIDENGANIMPLEMENTASI AKUNTANSI BERBASIS AKRUAL SEBAGAI VARIABEL INTERVENING (STUDI PADA KANTOR PUSAT KEMENTERIAN PERHUBUNGAN) - Eka C Setyawan; Dian Rustiani; Nabilah Nawazir; Sally Marcelina; Veronica Phang; Novita Lumanaw; Erikson Erikson; Haryono Umar (Lembaga Penelitian Universitas Trisakti, 2019)
This study aims to analyze the influence of SPIP (Government Internal ControlSystems) and Internal Audit on corruption prevention mediated by theimplementation of accrual-based accounting at Ministry of Transportations of TheRepublic of Indonesia. The type of research used was descriptive and causal.The research method used was questionnaire, with the scope of employees inthe field of Internal Audit and Accounting, which consists of Senior Auditors andStructural Officials in the field of accounting at the Head Office of the Ministry ofTransportation as many as 91 respondent. The analysis data is processed usingSPSS ver.23.0.The results of the research shows that the SPIP has no significanteffect (indirectly) on prevention of corruption through the implementation ofAccrual-Based Accounting, while Internal Audit has a significantly indirect effecton Corruption Prevention through the implementation of Accrual-BasedAccounting.